Operational Competitiveness Development and Its Risk Evaluation - Liu, Yang; Takala, Josu (Journal on Innovation and Sustainability. RISUS ISSN 2179-3565, 2011)
This paper connects previous research in global competitiveness analysis, taking the impact of global financial crisis into account, to evaluate how manufacturing companies are able to manage crisis by adjusting their manufacturing strategy and transformational leadership together with technology level, and develop their operational competitiveness through Sense & Respond (S&R) for dynamic decisions to optimize resource allocations and adjust strategies. It develops a theoretical approach of integrating the core factors which influence operational performance into conceptual analytical models to evaluate overall competitiveness and the risks arisen from adjustments. The empirical studies are focused to compare manufacturing companies in Finland with benchmarking to China, Slovakia, Iceland, and Spain to conclude the development of operational competitiveness.